2006
DOI: 10.1088/0953-2048/19/7/s34
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the field-trapping capabilities of bulk Nd–Ba–Cu–O superconductors using Ba–Cu–O substrates

Abstract: We used Ba–Cu–O substrates to fabricate bulk Nd–Ba–Cu–O superconductors using a top-seeded melt-growth method. There were several advantages for the use of Ba–Cu–O substrate compared to conventional substrate materials such as MgO, ZrO2, Al2O3, RE123 and RE211 (RE =  rare earth). The Ba–Cu–O did not react with the precursor and minimized liquid loss. Accordingly, the introduction of large-sized cracks was suppressed. We also found that Tc values were high at the bottom regions, which was ascribed to the benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…It was found that a suitable choice of the substrate material layers can minimize the chemical contamination. 22 When Ba-Cu-O powders were inserted between the bulk precursor and a substrate material like Y 2 O 3 , chemical reaction was completely suppressed. Furthermore, the trapped field values of Gd123 and Nd123 bocks on the back side were higher than those of the top sides.…”
Section: Large-grain Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that a suitable choice of the substrate material layers can minimize the chemical contamination. 22 When Ba-Cu-O powders were inserted between the bulk precursor and a substrate material like Y 2 O 3 , chemical reaction was completely suppressed. Furthermore, the trapped field values of Gd123 and Nd123 bocks on the back side were higher than those of the top sides.…”
Section: Large-grain Samplesmentioning
confidence: 99%
“…Fault Current Limiters: Power systems are occasionally beset by large transient current increases (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) times the rated values) caused by lightning, short circuits, and other faults. It is important to limit the duration and size of the fault current to prevent destruction of power equipment in the system by overheating and large electromagnetic forces.…”
Section: Conductor Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although such TSMG-processed bulk superconductors could exceed 3 T in trapped magnetic field for a top surface at liquid nitrogen temperature [5], largesized cracks affecting a trapped magnetic field distribution are readily formed by such as porosity, segregation, microcracks, thermal stress and oxygen annealing for transformation to a superconducting phase when enlarging the size of bulks. In particular, a long-time thermal treatment around the peritectic temperature caused a reaction between and/or a fixing of bulk bottom surfaces and substrate materials, which was a key trigger of cracking due to a concentration of thermal stress and a brittleness of reacted regions [6]. Furthermore, such a reaction of precursors with substrate materials at the bottoms increased liquid loss and then degraded field-trapping capabilities and superconducting properties [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the production of this type of single domain with a diameter larger than 50 mm encounters technological difficulties such as a slow growth rate and a relatively narrow growth window, resulting in unwanted spontaneous nucleation during the growth process. In order to overcome those difficulties some research groups [1][2][3] are now making an effort to develop a new generation of light rare-earth barium-cupper-oxide (LReBCO) bulk superconductors, where Re = Nd, Sm, Eu and Gd, which is believed to exhibit high T c and J c and a faster growth rate than YBCO. Other groups [4][5][6][7][8] are interested in developing a new type of generic seed crystal to produce large single domain bulks of Y-and LRe-based materials.…”
Section: Introductionmentioning
confidence: 99%